Discovering Netflix: brand identity and representations of diversity - Pedro, Josep (2022)
This article analyzes Netflix's strategic identification with the notion of diversity, both off-screen and on-screen. Drawing on its public communications, on industry reports and on the literature about the subject, it focuses on two dimensions: the relationship between diversity, inclusion, company policy and Netflix’s brand identity, emphasizing workforce diversity (off-screen); and the diversity of its content based on the broad category of Netflix Originals, considering diversity of place, gender and ethnicity or “race” (on-screen). Thus, the text critically reveals multiple complementary strategies, increasingly employed globally to build a brand identity linked to diversity as a positive value that is reclaimed in the 21st century. Through this brand identification with diversity, Netflix seeks to distinguish itself from both the traditional audiovisual industry and from its competitors, contributing to its hegemony in the global video-on-demand market.